Upregulation of ETV2 Expression Promotes Endothelial Differentiation of Human Dental Pulp Stem Cells. (29th January 2021) - Li, Jing; Zhu, Youming; Li, Na; Wu, Tao; Zheng, Xianyu; Heng, Boon chin; Zou, Duohong; Xu, Jianguang
The lack of vasculogenesis often hampers the survivability and integration of newly engineered tissue grafts within the host. Autologous endothelial cells (ECs) are an ideal cell source for neovascularization, but they are limited by their scarcity, lack of proliferative capacity, and donor site morbidity upon isolation. The objective of this study was to determine whether differentiation of human dental pulp stem cells (DPSCs) into the endothelial lineage can be enhanced by recombinant ETV2 overexpression. DPSCs were extracted from fresh dental pulp tissues. ETV2 overexpression in DPSCs was achieved by lentiviral infection and cellular morphological changes were evaluated. The mRNA and protein expression levels of endothelial-specific markers were assessed through quantitative real-time polymerase chain reaction, western blot, immunofluorescence staining, and flow cytometry. The tube formation assay and Matrigel plug assay were also performed to evaluate the angiogenic potential of the ETV2-transduced cells in vitro and in vivo, respectively. Additionally, proteomic analysis was performed to analyze global changes in protein expression following ETV2 overexpression. After lentiviral infection, ETV2-overexpressing DPSCs showed endothelial-like morphology. Compared with control DPSCs, significantly higher mRNA and protein expression levels of endothelial-specific genes, including CD31, VE-Cadherin, VEGFR1, and VEGFR2, were detected in ETV2-overexpressing DPSCs. Moreover, ETV2 overexpression enhanced capillary-like tube formation on Matrigel in vitro, as well as neovascularization in vivo . In addition, comparative proteomic profiling showed that ETV2 overexpression upregulated the expression of vascular endothelial growth factor (VEGF) receptors, which was indicative of increased VEGF signaling. Taken together, our results indicate that ETV2 overexpression significantly enhanced the endothelial differentiation of DPSCs. Thus, this study shows that DPSCs can be a promising candidate cell source for tissue engineering applications.